2015
DOI: 10.4236/acs.2015.51002
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Parameters of Ambient Air Quality in National Capital Territory (NCT) of Delhi (India)

Abstract: Air Pollution is an escalating problem worldwide fuelled by increasing anthropogenic activities, speedy development, rapid industrialization, transportation, superfluous use of fossil fuel consumption, increasing global power needs, etc. Also the diverse meteorological factors influence our environment to a great extent. Population explosion has led to remarkable increase in vehicular population. The use solely depends upon the lifestyle of the citizen. Any change in the lifestyle has a remarkable effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Recently Gour et al (2015) published a detailed report based on 5 years of observation that in New Delhi CO and NO x concentration is lower on weekends and public holidays than during working days. This further suggested that both of the species are related with traffic source.…”
Section: Ambient Aerosol Measurementmentioning
confidence: 99%
“…Recently Gour et al (2015) published a detailed report based on 5 years of observation that in New Delhi CO and NO x concentration is lower on weekends and public holidays than during working days. This further suggested that both of the species are related with traffic source.…”
Section: Ambient Aerosol Measurementmentioning
confidence: 99%
“…Similarly, more recently a DMA-APM approach to get particle size and mass information, respectively has been extensively applied for particle density measurements in different environments (Geller et al, 2006;Malloy et al, 2009;Lee et al, 2009;Gysel et al, 2011;Nakao et al, 2013;Rissler et al, 2014;Yin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oxides of nitrogen include nitrogen dioxide (NO 2 ) High levels of exposure have been linked with increased hospital admissions due to respiratory problems, while long-term exposure may affect lung function and increase the response to allergens in sensitive people Carbon monoxide (CO) when inhaled, blocks oxygen from the brain, heart, and other vital organs. Fetuses, new-born children, and people with chronic illnesses are especially susceptible to the effects of CO [32]. Carbon monoxide reduces the blood's oxygen-carrying capacity which can reduce the availability of oxygen to key organs.…”
Section: Parameters Of Vehicular Pollutionmentioning
confidence: 99%